The Socio-Economic Context of Africa and its Impact on Doping and Anti-Doping - (:unkn) unknown (My University, 2024)
The fight against doping is organized at the global level under the aegis of the World Anti-Doping Agency (WADA) in application of the 2005 UNESCO convention which made the application of the World Anti-Doping Code mandatory for all countries wishing to participate and organize international sports competitions. In fact, it appears that for a variety of reasons, the application of the World Anti-Doping Code is largely theoretical in Africa. Indeed, if most African countries adhere to the system set up by WADA, it appears that very few are able to apply it effectively. The numerous difficulties that African countries may experience due to a degraded socioeconomic context confine anti-doping policies to the rank of non-priority public policies. Thus, the difficulties experienced by different countries in terms of development, structuring of the sports movement through associations, public administration, public health and corruption must lead us to consider that the fight against doping in Africa cannot be free of the socioeconomic context and must therefore be adapted accordingly. This adaptation must be based on the reality of the functioning of sports organizations in the countries and not on theoretical considerations that are far removed from reality.
Keywords: African Research